1977
DOI: 10.1107/s0567740877012229
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of magnesium dimolybdate

Abstract: The structure of magnesium dimolybdate, MgMo207, monoclinic with space group P2/c and a = 8.111 (2), b = 5.700 (1), c = 15.002 (3) ,~, fl = 115.26 (2) °, Z = 4, was determined by the heavy-atom method and refined by full-matrix least squares to an R of 0.095 for 2558 counter reflexions. The Mo202-pyro-anion consists of two corner-sharing MoO 4 tetrahedra, which are twisted from the ideal eclipsed configuration by an average of 12.3 °. Mo207 groups form anionic sheets parallel to the (100) plane. Mg 2÷ ions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…For the isotypic compound K 3 (Mo 2 O 7 )Br, see: Becher & Fenske (1978). For dimolybdates with similar condensed anions made up of MoO 4 tetrahedra, see: Ce 2 (MoO 4 ) 2 -(Mo 2 O 7 ) (Fallon & Gatehouse, 1982); Mg 2 Mo 2 O 7 (Stadnicka et al, 1977). Table 1 Selected bond lengths (Å ).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For the isotypic compound K 3 (Mo 2 O 7 )Br, see: Becher & Fenske (1978). For dimolybdates with similar condensed anions made up of MoO 4 tetrahedra, see: Ce 2 (MoO 4 ) 2 -(Mo 2 O 7 ) (Fallon & Gatehouse, 1982); Mg 2 Mo 2 O 7 (Stadnicka et al, 1977). Table 1 Selected bond lengths (Å ).…”
Section: Related Literaturementioning
confidence: 99%
“…(2009). E65, i87 [doi:10.1107 Stadnicka et al, 1977). The corner linkage of tetrahedra is associated with bond-length distortions: the <Mo -O1> bond length is 1.725 (4) Å, whereas the <Mo-O2> bond-length is 1.8764 (7) Å; the O-Mo-O bond angles range from 108.34 (14)° (for <O1-Mo-O1>) to 110.58 (13)° (for <O1-Mo-O2>).…”
Section: Supporting Informationmentioning
confidence: 99%
“…MgMo 2 O 7 (prepared by the procedure in Ref. (20)), Al 2 (MoO 4 ) 3 (GFS Chemicals, 99%), (NH 4 ) 2 Mo 2 O 7 (Strem Chemicals, 99.98%), and Mo 2 C (prepared as in Ref. (21)) were diluted with SiO 2 to 4 ± 0.5 wt% Mo, pressed into wafers, and sealed in Kapton tape (3M Co.).…”
Section: Mo K-edge X-ray Absorption Spectroscopymentioning
confidence: 99%
“…The refined value of S 2 0 was 0.63. are in octahedral sites (38), described poorly the experimental spectrum. The MgMo 2 O 7 structure (20), in which both Mo atoms are tetrahedrally coordinated and connected via a bridging oxygen, provided a much better starting point when Al replaced the Mg atom. The fragment upon which the refinement was based is shown in Fig.…”
Section: Extended X-ray Absorption Fine Structurementioning
confidence: 99%
“…In fact, a great variety of X-O-X bond angles were determined by X-ray for the same X 2 O 7 unit with different cations [6]. For example, while in K 2 Mo 2 O 7 ·KBr the Mo-O-Mo linkage is linear [7], the Mo 2 O 7 2Ϫ ion in MgMo 2 O 7 shows a bridge bond angle of 160.7Њ [8]. In a recent publication, Griffith et al [9] concluded that the Mo-O-Mo linkage in Mo 2 O 7 2Ϫ hydrogen-bonded to binaphthol units is bent and that the initially suggested linear structure results from a significant thermal anisotropy exhibited by the bridging oxygen atom.…”
Section: Introductionmentioning
confidence: 99%